Implementasi Sikap Toleransi Antar Umat Beragama Di Desa Jarak Kecamatan Wonosalam Kabupaten Jombang - Dhian Satria Yudha Kartika; Affiva Lindi Damayanti; Afifah Nur Azisah; Fotinus Wahyudi Josiriz (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Tolerance in the dynamics of Indonesian society and socio-cultural diversity is needed. One of the villages in Indonesia that implements its tolerance values well is the Village of Distance, Wonosalam District, Jombang Regency. Distance Village is a village where the people have diverse beliefs, which consist of Christianity, Hinduism and Islam. This research was conducted with the aim of describing the manifestation of inter-religious tolerance in the Distance Village and to see the community's efforts to maintain an attitude of tolerance between religions in the Distance Village. The research carried out uses qualitative methods, in which the researcher will go directly to the field to become the main instrument in carrying out observation and interview activities both on the grand tour question, the data selection stage, conducting data collection, analysis and making conclusions. The technique used in the data collection process is by means of observation, documentation and direct interviews. The results of the research conducted show that the people of the Distance Village who have various religions can live side by side in harmony and respect each other, especially in terms of worship and social activities. The form of religious tolerance in the village of Distance can be seen in the activities of the village community at the moment of religious holidays and in the culture of mutual cooperation in carrying out community social activities. Then, for their own efforts, it can be seen when the people of the Distance Village maintain an attitude of tolerance by respecting each other regardless of religion.